Evaluation of Knowledge, Attitude, Practice and Hospital Experience Regarding COVID-19 among Post-partum Mothers at a Tertiary Care Center: A Cross-sectional Study - Adhikari, S.P.; Pariyar, J.; Sapkota, K.; Gurung, T.K.; Adhikari, S.R. (Kathmandu University Medical Journal, 2020)
Background: Pregnant and breastfeeding women are more susceptible to viral infection and in the year 2020 they have to face the COVID-19 pandemic. Since, no successful treatment and vaccine has been developed so far, efforts to enhance the knowledge, attitudes, and practice of the public, especially the high-risk groups like pregnancy and postpartum period are crucial to manage COVID-19 pandemic. Objective To analyze the knowledge, attitude, practice and hospital experience regarding COVID-19 among post-partum mothers at a tertiary care center of Nepal Method The data collection was based on direct interview after receiving written consent from the research participants, using a semi-structured questionnaire. The questionnaire consisted of 4 major domains- knowledge (8 questions), attitude (6 questions), practice (5 questions) and experience (5 questions). Standard descriptive statistics were used for the data, mean and standard deviation for continuous variables whereas frequencies and percentages for categorical variables. Result A total of 203 post-partum women participated in the study. Almost all the participants had heard about COVID-19 (96.6%). A majority of them were aware about how COVID-19 gets transmitted and its preventive measures. Most of the participants (88.2%) knew that COVID-19 has effects on pregnancy. Almost all of participants (97%) wore mask during hospital stay. All of the women washed their hands with soap water or alcohol based sanitizer. A majority of the mothers (79.3%) wore mask while breastfeeding their baby. Conclusion The post-partum mothers have good knowledge, attitude, practice and experiences regarding the COVID-19 pandemic.